UNJUK KERJA PEREDAM GELOMBANG VARIASI TIPE PANTAI LANDAI DAN PARABOLA BERPORI PADA TANGKI GELOMBANG LABORATORIUM TEKNOLOGI KELAUTAN - Mustadir, Ademulya Wardana (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2022)
unstable global climate change, sea waves can damage coastal areas and buildingssurrounding. Wave dampers are needed to reduce the energy of incident waves and reflected wavesexcessive and undesirable in water areas. The effectiveness of wave dampers for sloping beach typesand porous parabolas to dampen reflected water waves are the objectives of this study. This researchcarried out at the Marine Technology Research Laboratory, Hasanuddin University. Regular waves are tested inwave flume with a length of 25 m, a width of 1 m and a depth of 1.2 m which is equipped with a wave generatorflaps type. The wave absorbers at the other end are made of 20 cm thick foam and mounted onporous steel cross-section with a porosity of 0.155091. The eight wave probe points are placed together along the lengthwave flume. Wave probe 8 is placed as far as the wavelength from the wave damper and is 1/8 awaywavelength between probes 1-8. Water level fluctuation data is processed to obtain wave height in eachwave probe using zero up crossing method. To test the performance of this wave damper, performedtests and their reflection coefficients are compared with other theoretical and experimental models. Testlaboratory is carried out to acquire wave data and numerical data processing is carried out forclarify results. Wave damping experiments carried out in the laboratory produce dampingrelatively good waves where the reflection coefficient values obtained on average are below 0.2 (Hr/Hi) willbut the performance of the wave damper in the laboratory is not as effective as the damper using chunk mediastone so further development and analysis is needed.